2002
DOI: 10.1124/jpet.301.2.451
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transmembrane Helix 5 in Agonist Binding to the Human H3 Receptor

Abstract: We have used alanine scanning mutagenesis to identify residues in transmembrane domain 5 of the histamine H3 receptor that are important for agonist binding. All of the mutants generated were functionally expressed as demonstrated by their ability to bind [125 I]iodoproxyfan with comparable affinity to the wild-type receptor and their ability to inhibit forskolin-stimulated cAMP formation when activated by histamine. Many mutations produced small changes in the potency of histamine, but the most pronounced red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 25 publications
5
95
0
Order By: Relevance
“…Several rotamers were considered for each residue, for which no definite placement could be obtained by applying the SCWRL algorithm and which was likely participating in the binding site. The approximate position of antagonists in the hH 3 R binding pocket was thereby known from mutational studies, which showed that D3.32 and E5.46 were the major sites of interaction [22]. During docking FUB836 into all alternative binding sites, a distance constraint between the piperidyl-nitrogen of FUB836 and D3.32 was applied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several rotamers were considered for each residue, for which no definite placement could be obtained by applying the SCWRL algorithm and which was likely participating in the binding site. The approximate position of antagonists in the hH 3 R binding pocket was thereby known from mutational studies, which showed that D3.32 and E5.46 were the major sites of interaction [22]. During docking FUB836 into all alternative binding sites, a distance constraint between the piperidyl-nitrogen of FUB836 and D3.32 was applied.…”
Section: Resultsmentioning
confidence: 99%
“…Another residue showing a similar ''unstable'' behaviour was F5.47, which adopted a rotamer pointing into the binding pocket during the simulation of uncomplexed hH 3 R models. For the F5.47A variant a significant drop in potency was observed suggesting that this residue was involved in upholding the receptor structure or in receptor activation [22]. In simulations of antagonist/hH 3 R complexes the conformational switch of F5.47 towards the inside of the binding pocket was inhibited due to the presence of the ligand.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A bovine rhodopsin based model of the H3R was used to investigate the role of TM5 residues in ligand binding [36]. Mutation of Glu206(5.46) showed reduction of affinity and potency of several agonists, such as histamine, R-α-methylhistamine, imetit and impentamine.…”
Section: H3 Receptormentioning
confidence: 99%
“…The role of individual residues in transmembrane helices has been traditionally addressed by scanning mutagenesis (generally Cys-or Ala-scanning mutagenesis), where the TM residues are substituted, one at a time, and the functional and/or structural consequences of the substitutions are investigated (Kaback et al, 2001;Frillingos et al, 1998;Lu et al, 2001;Uveges et al, 2002). In the case of one of the better studied membrane proteins, the lactose permease of E. coli (12 TMs), it has been established that only 6 of its 417 amino acids are essential for function and cannot be replaced with any other residue (Kaback et al, 2001;Abramson et al, 2003).…”
Section: Replacement Of the Tm Segments Alters Packing And Functionalitymentioning
confidence: 99%